A novel fetal Doppler calibrator: enhancing the precision of fetal heart rate monitoring - Fauzi, Ekha Rifki; Setiyadi, Noor Alis; Doungjan, Kamonthip (International Journal of Power Electronics and Drive Systems (IJPEDS), 2025)
The congenital heart disease is associated with abnormal brain development in the womb of pregnant women where fetuses with congenital heart disease are at higher risk of miscarriage compared to the general population. Fetal and neonatal risk identification and assessment are essential for comprehensive risk stratification after diagnosis of congenital heart disease. This study aims to improve the accuracy of Doppler fetal measurements in the diagnosis of congenital heart disease risk with calibrators. This study used an experiment of a calibrator with four push buttons embedded to increase and decrease the beat per minute (BPM) value by comparing the BPM value of the Doppler fetal. The measurement was carried out by comparing the values of the calibrator and the Doppler fetal with units and tens of BPM. Statistical analysis used the paired sample T-Test. The measurement obtained a significant p-value of <0.05 with 95% CI. Furthermore, this calibrator does not have a difference in accuracy level with a Doppler fetal. This states that the calibrator has the feasibility to calibrate the fetal Doppler in the fetal heart examination service for pregnant women. This study has the prospect of improving the technology with the embedding of the internet of things (IoT).